Condensation and protamination of sperm chromatin affect ICSI outcomes when gametes from healthy individuals are used. Issue 3 (20th December 2022) - Ribas-Maynou, Jordi; Novo, Sergi; Salas-Huetos, Albert; Rovira, Sergi; Antich, Marta; Yeste, Marc
Abstract: STUDY QUESTION: Do defects in sperm chromatin protamination and condensation have an impact on ICSI outcomes? SUMMARY ANSWER: Sperm protamination is related to fertilization rates in healthy donors, and the in vitro capacity of sperm to condense their chromatin is linked to blastocyst rates, both associations being more apparent in women <33 years of age. WHAT IS KNOWN ALREADY: Previous data on how sperm chromatin damage affects ICSI outcomes are inconsistent. Revealing which sperm factors influence embryo development is necessary to understand the male contribution to ICSI success and to develop novel sperm selection techniques or male-based treatments. Sperm chromatin is mainly condensed in protamines, which are cross-linked through disulphide bridges. This study aimed to determine whether sperm protamination and the integrity of disulphide bonds (condensation) are related to embryo development after ICSI. STUDY DESIGN, SIZE, DURATION: The design was a retrospective study with a blind analysis of sperm chromatin. Gametes were divided into two groups: double donation (DD) cohort and single donation (SD) cohort. Samples from 45 semen donors used in 55 ICSI cycles with oocyte donors (age range 19–33 years), generating 491 embryos, were included in the DD cohort. The SD cohort consisted of samples from 34 semen donors used in 41 ICSI cycles with oocytes from healthy females (single-parent families or lesbian couples, age range 20–44 years), generating a total of 378 embryos. PARTICIPANTS/MATERIALS, SETTINGS, METHODS: Donor sperm samples from DD and SD cohorts were used for standard ICSI, and embryo development was observed by time-lapse imaging. The incidence of thiol reduction (dibromobimane, DBB) and the degree of chromatin protamination (chromomycin A3, CMA3, indicating non-protaminated regions) in sperm were determined by flow cytometry at 0 and 4 h post-thawing. MAIN RESULTS AND THE ROLE OF CHANCE: Percentages ± standard deviation of CMA3 were 21.08 ± 9.09 and 35.01 ± 14.68 at 0 and 4 h post-thawing, respectively, in the DD cohort and 22.57 ± 9.48 and 35.79 ± 12.58, at 0 and 4 h post-thawing, respectively, in the SD cohort. Percentages of DBB + were 16.57 ± 11.10 and 10.51 ± 8.40 at 0 and 4 h post-thawing ( P  <   0.0001), respectively, in the DD cohort and 17.98 ± 10.19 and 12.72 ± 8.76 at 0 and 4 h post-thawing ( P  <   0.0001), respectively, in the SD cohort. Female age correlated with fertilization rates, and the relation between sperm chromatin and embryo development was determined through multiple linear regression. While CMA3 was associated with fertilization rates, with no influence of female age, in the DD cohort (β1 = −1.036, P  <   0.001 for CMA3 ; β2 = 0.667, P  =   0.304 for female age), this was not observed in the SD cohort, where female age had a significant effect, masking the effects of CMA3 (β1 = −0.066, P  =   0.804 for CMA3 ; β 2 = −1.451, P  =   0.003 for female age). The in vitro capacity of sperm to condense their chromatin after 4 h of incubation was associated with blastocyst rates, independent of female age (DD cohort: β1 = −0.238, P  =   0.008 for %DBB + variation; β2 = 0.404, P  =   0.638 for female age; SD cohort: β1 = −0.278, P =  0.010 for %DBB + variation; β2 = −0.292, P  =   0.594 for female age). The in vitro capacity of sperm to condense their chromatin was also related to the time required for the embryo to reach blastocyst stage in the DD cohort ( P  =   0.007). Finally, multiple logistic regression showed that both chromatin protamination and condensation, together with the age of the oocyte donors and the embryo recipients, had an impact on pregnancy achievement ( P  <   0.01) and on live birth rates ( P  <   0.01). LIMITATIONS, REASONS FOR CAUTION: The main limitation was the restrictive selection of couples, which led to a relatively small sample size and could influence the observed outcomes. For this reason, and to reduce Type I error, the level of significance was set at P ≤  0.01. On the other hand, the use of cryopreserved samples could also be a limitation. WIDER IMPLICATIONS OF THE FINDINGS: This research demonstrated that protamination and condensation of sperm chromatin are related to embryo development after ICSI, but female age could be a confounding factor when oocytes from older females are used. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the European Union's Horizon 2020 Research and Innovation scheme under the Marie Skłodowska-Curie grant agreement No 801342 (Tecniospring INDUSTRY; TECSPR-19-1-0003); La Marató de TV3 Foundation (214/857-202039); the Ministry of Science and Innovation, Spain (IJC2019-039615-I); the Catalan Agency for Management of University and Research Grants, Regional Government of Catalonia, Spain (2017-SGR-1229); and the Catalan Institution for Research and Advanced Studies, Spain (ICREA). The authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A.